The role of fear of missing out in shaping consumption behavior and its implications for the resilience of gastronomic tourism in Sumedang Regency - Widya Alya Fatimah; Gilang Pratama Putra; Oman Sukirman (School of Tourism, Universitas Ciputra Surabaya, 2026)
The development of social media has led to the emergence of the Fear of Missing Out (FoMO) phenomenon, which influences consumption behavior, including in culinary tourism. This study aims to analyze the role of FoMO in shaping consumption behavior and its implications for the resilience of gastronomic tourism in Sumedang Regency. This study uses a qualitative approach through in-depth interviews, observation, and documentation with community informants, business actors, and tourism policymakers, then analyzed thematically using NVivo. Research in Sumedang Regency indicates that FoMO (Focus on Motivation) acts as an initial trigger that encourages consumers to try viral culinary delights. However, FoMO-based consumption is temporary and does not directly build loyalty. The sustainability of gastronomic tourism is more determined by the quality of the experience, including taste, consistency, price, consumer recommendations, and cultural values, which influence satisfaction and repeat purchases. This study demonstrates that the influence of FoMO on the sustainability of gastronomic tourism is indirect but rather mediated by consumer experience and satisfaction. These findings emphasize the importance of culinary tourism development strategies that focus not only on trends but also on quality and sustainability.